PENGARUH PERILAKU OPPORTUNISTIK, MEKANISME PENGAWASAN, DAN FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA - Rosia Sari, Alamanda; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2017)
Earnings Management is an action on managing earnings that are usually done by the management, especially managers. Earnings management occurs when management uses its consideration in preparing financial statements using generally accepted on accounting procedures. The existence of a flexibility in choosing accounting policy is possible to create an opportunity for managers to manage profit in order to maximize their utility and cause agency problems. In this research there are several factors that can motivate management to manage the company profit. The study aims to examine the relationship between opportunistic behavior (Free Cash Flow and Profitability), Monitoring Mechanism (Leverage) and Financial Distress toward Earnings Management. The population of this study is Manufacturing Companies which have been list in Indonesia Stock Exchange year 2013-2015. Sampling of company is done by using purposive sampling method in accordance with predetermined criteria. There are 40 companies from 138 population of the company sampled in this study. The analytical tools that used in this research is using Multiple Regression Analysis.The results of this study indicate that the opportunistic behavior measured on the proxy of profitability significantly positive effect on Earnings Management. This indicates that the increasing opportunistic behavior of a manager will increase earnings management practices. However, it is different with opportunistic behavior as measured by free cash flow, which in fact shows a reverse relationship that can reduce earnings management. The existence of a monitoring mechanism by the Principal does not have a significant effect on earnings management. Meanwhile, the existence of Financial Distress conditions is positively affect the earnings management, so this shows the increase in earnings management occurs.